Voronin S.V. Evaluation of bearing capacity and friction coefficient of the nematic boundary layer. - Воронін, С.В. (Problems of Tribology, 2014)
Among the wide range of functional additives that are added to the liquid lubricants there is a specific class of substances that can form in nonpolar hydrocarbon solutions of liquid crystal phase as embryos nanometer dimensions. The presence of lubricant additives such environments results in the process of greasing friction units to form on the surface polymolecular boundary films with layered structure , each layer of which is a solid or liquid molecular crystals , and its degree of order depends on the distance to the surface friction. Limiting molecular film which is influenced by the force field friction surface has a different degree of ordering of molecules - the maximum for monolayer , the minimum for the isotropic liquid. Accordingly, the degree of order to vary the properties of the film on its thickness , and the transition from one phase to the other properties will vary jumps. Studying the properties of each individual phase boundary layer is the actual problem , as it will allow to predict the tribological properties of friction units working under different loads and temperatures in the presence of the boundary film layered structure. The paper describes the method of calculation of the bearing capacity and specific strength and coefficient of friction in the boundary layer of the nematic film that forms on the surfaces of friction. It was established that the main factors that affect the carrying capacity of nematic layer is the dipole moment of the molecules, their size and relative positions in the layer. In force and friction coefficient in nematic layer also significantly affects the surface tension force field that prevents rotation of the molecules under the action of tangential external load.